Identification of potent new brain cancer EGFR inhibitor from usimine A and usimine B: computer-aided drug design perspective - Roney, Miah; Issahaku, Abdul Rashid; Wilhelm, Anke; Mohd Fadhlizil Fasihi, Mohd Aluwi (AMG Transcend Association, 2024)
Brain cancer ranks 10th among cancer-related causes of death for patients worldwide. Medical chemists still have many challenges because of the high side effects, increasing tumor resistance, and low selectivity of new chemotherapeutic medications despite the enormous effort put out to extract, develop, and synthesize them. The anti-cancer potential of many natural substances has garnered significant research in the past few decades. This study's main goal is to discover the anti-cancer activity of Usimine A and Usimine B against the EGFR protein of brain cancer using the in-silico approaches. In this study, the biological features of Usimine A and Usimine B were determined using the PASS prediction tool, and the pIC50 value was predicted to know the activity of these compounds. Furthermore, molecular docking and dynamic simulations were performed to see the binding affinity and stability of the docking complexes. Usimine A and Usimine B have the PASS prediction score of 0.835<Pa<0.002 and 0.851<Pa<0.002, respectively. Additionally, the QSAR analysis demonstrated that both compounds have respective pIC50 values of 4.82 and 4.74. Furthermore, the docking calculations demonstrated the remarkable efficacy of Usimine B (-7.3 kcal/mol) as an EGFR inhibitor of brain tumors. This compound exhibited five hydrogen bonds with the residues of Leu792, Met793, Asn842, Thr854, and Val843 in the active site of EGFR protein. A 200 ns molecular dynamic simulation demonstrated the stability of the Usimine B-EGFR complex compared to the reference complex (Gefitinib-EGFR). Furthermore, the thermodynamic calculations of the Usimine B-EGFR complex exhibited a binding affinity of -28.69± 3.50 kcal/mol for the EGFR protein. The results show that Usimine B has been identified as an inhibitor of brain cancer against EGFR protein. As part of the process of identifying and developing a novel medicine against brain cancer, more studies on in vitro and in vivo Usimine B is advised.